Schaum's Electromagnetics Supplementary Problem 8-44: Parameters in Parallel-plate Capacitor - Mitra-Kirtley, Sudipa (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how some physical quantities change in a parallel-plate capacitor when the separation distance between plates is altered.